Knowledge about age-related decline in fertility and oocyte cryopreservation: A national survey - Karissa C Hammer; Alyssa N Kahan; Louis F Fogg; Mark A Walker; Jennifer E Hirshfeld-Cytron (Wolters Kluwer Medknow Publications, 2018)
Context: Women worldwide are delaying childbearing, but are they aware of the age-related decline in fertility? Aims: The aim of this study is to investigate awareness of age-related decline in fertility and oocyte cryopreservation. Settings and Design: A primary analysis of a cross-sectional electronic survey with a nationally representative sample of nulliparous women aged 25-45 years. Subjects and Methods: A national online survey performed March 4-March 9, 2016. Statistical Analysis Used: A linear regression model and ANOVA tests were performed. Results: A total of 1213 women completed the survey. A significant difference was discovered in fecundity knowledge between women who identified as in a partnership compared to those who did not. Partnered women were more likely to respond "know a lot" about the age-related decline in fertility, whereas unpartnered women were more likely to respond "never heard of it" (P < 0.01). Partnered women are also more likely to respond that they would have made different life choices had they been more knowledgeable about fertility at a younger age (P = 0.01). The majority of the survey population had heard of oocyte cryopreservation but did not know much about it. Conclusions: Slightly over half of participants had an understanding of the natural age-related decline in fertility. Having a partner significantly increased the likelihood that a woman reported more knowledge about fertility. More effort is necessary to educate all women on assisted reproductive technologies and the natural age-related decline in fertility, specifically single women of childbearing age.